Disciplinary Strategies, Corruption Control and the Performance of the Nigeria Police Force in Owerri Metropolis - Nnajieto, Augustina Onyedikachi; Nnajieto, Charles Chibuzor (Asian Journal of Science, Technology, Engineering, and Art, 2025)
This study examines disciplinary strategies, corruption control, and the performance of the Nigeria Police Force in Owerri Metropolis against the backdrop of growing concerns over indiscipline and misconduct among police officers, which have eroded public trust and undermined effective law enforcement. The objective is to assess how disciplinary measures influence performance, professionalism, and integrity within the Force. Guided by three research objectives, questions, and hypotheses and anchored in Ethics and Reinforcement theories, the study surveyed a population of 850 officers, from which a sample of 272 was selected using the Taro Yamane formula. Data were collected through a structured questionnaire and analysed using frequency distributions, simple percentages, and chi-square statistical tests. The findings indicate that disciplinary strategies, including the suspension of fraudulent officers, demotion of dishonest officers, and dismissal of untrustworthy officers, significantly enhance the performance of the Nigeria Police Force in Owerri Metropolis by promoting accountability and deterring misconduct. The study concludes that robust, consistently enforced disciplinary measures are critical for strengthening professionalism, integrity, and public confidence in the police. It recommends improved welfare packages to reduce disciplinary infractions and enhance morale, restructuring and sanitizing the police force to foster ethical conduct and public trust, periodic training on human rights, community policing, and conflict resolution, as well as a more rigorous recruitment process to prevent the enlistment of individuals with questionable character.